1999
DOI: 10.1136/pgmj.75.886.481
|View full text |Cite
|
Sign up to set email alerts
|

A lesson in the management of testicular cancer in a patient with a solitary testis

Abstract: SummaryFive per cent of patients with germ cell tumours of the testis will develop a further tumour in the contralateral testis. Standard treatment in such cases is a second orchidectomy, resulting in infertility, hormone replacement, and psychological morbidity. In this case report we explore the role of testis conservation in these patients and also show that there is a risk of removing a potentially normal testis if a histological diagnosis is not sought prior to orchidectomy.Keywords: testicular germ cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Despite the very small tumours (mean 3.6 mm in diameter) the ratio of benign to malignant lesions in the present series (Table 1) compares well with that of previous studies including larger incidental tumours [15,17]. In a study by Horstman et al [15] including nine impalpable incidental testicular tumours, seven were found to be benign stromal tumours and two were malignant germ cell tumours; in that study the mean tumour diameter was significantly larger, at 8.8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) mm. Another study by Leroy et al [17] included 15 patients, with a mean tumour diameter of 7.5 (4-16) mm; histological analysis showed malignant germ cell tumour in four, while all other lesions were benign.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite the very small tumours (mean 3.6 mm in diameter) the ratio of benign to malignant lesions in the present series (Table 1) compares well with that of previous studies including larger incidental tumours [15,17]. In a study by Horstman et al [15] including nine impalpable incidental testicular tumours, seven were found to be benign stromal tumours and two were malignant germ cell tumours; in that study the mean tumour diameter was significantly larger, at 8.8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) mm. Another study by Leroy et al [17] included 15 patients, with a mean tumour diameter of 7.5 (4-16) mm; histological analysis showed malignant germ cell tumour in four, while all other lesions were benign.…”
Section: Discussionsupporting
confidence: 88%
“…epidermoid cysts) organ‐sparing surgery after frozen‐section analysis (FSA) has been widely accepted [3,4]. More recently, organ‐sparing procedures have been advocated also for treating malignant germ cell and stromal tumours in certain clinical settings [5–8]. Advanced ultrasound technology now provides images of higher resolution that allow the detection of extremely small intratesticular lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant or adjuvant chemotherapy have been used to permit conservative treatment. (Oliver et al, 1996;Sawyer et al, 1999). Testicular relapses were observed in that series of patients, but had no impact on survival.…”
Section: Discussionmentioning
confidence: 66%
“…1,55,62,[84][85][86][87] Selection criteria in these studies included: organ-confined disease with no infiltration of the rete testis; a mass of <2 cm in order to preserve testosterone-producing parenchyma; a negative postresection biopsy of the tumor bed; and conditions of cold ischemia to preserve the function of Sertoli and leydig cells. Heidenreich et al 55 treated 73 patients with GCT with partial orchiectomy using these criteria.…”
Section: Partial Orchiectomy Data Have Been Reported By the German Tementioning
confidence: 99%